Novel Therapeutics for Anthracycline Induced Cardiotoxicity - Vuong, Jacqueline T.; Stein-Merlob, Ashley F.; Cheng, Richard K.; Yang, Eric H. (Frontiers in Cardiovascular Medicine, 2022)
Anthracyclines remain an essential component of the treatment of many hematologic and solid organ malignancies, but has important implications on cardiovascular disease. Anthracycline induced cardiotoxicity (AIC) ranges from asymptomatic LV dysfunction to highly morbid end- stage heart failure. As cancer survivorship improves, the treatment of oncologic cardiotoxicities becomes more crucial to improve patient outcomes. Current treatment modalities for AIC have been largely extrapolated from treatment of conventional heart failure, but developing effective therapies specific to AIC is an area of growing research interest. This review summarizes the current evidence behind the use of neurohormonal agents, dexrazoxane, and resynchronization therapy in AIC, evaluates the clinical outcomes of advanced therapy and heart transplantation in AIC, and explores future horizons for treatment utilizing gene therapy, stem cell therapy, and mechanism-specific targets.